Schizophrenia Treatment with Second-Generation Antipsychotics: A Multi-Country Comparison of the Costs of Cardiovascular and Metabolic Adverse Events and Weight Gain - Kearns B (Dove Medical Press, 2021)
Benjamin Kearns, Katy Cooper, Anna Cantrell, Chloe Thomas School of Health and Related Research, The University of Sheffield, Sheffield, UKCorrespondence: Benjamin Kearns Email b.kearns@sheffield.ac.ukPurpose: Cardiovascular and metabolic adverse events are costly to treat, and their incidence is increased amongst people with schizophrenia, with different rates observed for second-generation antipsychotics. To inform treatment choice, this study sought to estimate the lifetime costs associated with antipsychotic choice, and how these costs varied across European countries.Methods: Systematic searches were conducted to identify evidence on effectiveness and costs. A Markov model was developed to assess the costs of ten antipsychotics: aripiprazole, brexpiprazole, cariprazine, lumateperone, lurasidone, olanzapine, paliperidone, quetiapine, risperidone and ziprasidone. Costs were obtained for seven countries: Italy, Hungary, France, Slovenia, Spain, Sweden and the UK. The costs considered were adverse events (including diabetes, myocardial infarction, stroke and weight gain), drug costs, relapse, treatment discontinuation and schizophrenia management. Two adult populations were modelled; initiating either acute or maintenance treatment, with a lifetime horizon for both.Results: Lurasidone was associated with the lowest lifetime costs amongst patients initiating acute treatment compared to all other atypical antipsychotics considered. The second lowest costs were for ziprasidone. These results were observed for all seven countries. The main drivers of cost differences were rates of diabetes and cardiovascular diseases, which were lowest for lurasidone, followed by ziprasidone then lumateperone. Costs for managing weight gain were lowest for lurasidone and ziprasidone. Similar results were observed for patients initiating maintenance treatment.Conclusion: Diabetes and cardiovascular events are large drivers of lifetime costs for people with schizophrenia. Lurasidone is predicted to have the lowest rates of these adverse events, and so the lowest costs amongst patients initiating acute treatment in seven European countries compared to nine other antipsychotics. Future research should investigate the individual costs of relapse management, including differences in the costs and proportions of hospitalizations.Keywords: cost analysis, side-effects, Europe, acute treatment, maintenance treatment